A novel homozygous variant of GPR98 causes usher syndrome type IIC in a consanguineous Chinese family by next generation sequencing - Chunli Wei; Lisha Yang; Jingliang Cheng; Saber Imani; Shangyi Fu; Hongbin Lv; Yumei Li; Rui Chen; Elaine Lai-Han Leung; Junjiang Fu (BMC, 2018)
Abstract Background Usher syndrome (USH) is a common heterogeneous retinopathy and a hearing loss (HL) syndrome. However, the gene causing Usher syndrome type IIC (USH2C) in a consanguineous Chinese pedigree is unknown. Methods We performed targeted next-generation sequencing analysis and Sanger sequencing to explore the GPR98 mutations in a USH2C pedigree that included a 32-year-old male patient from a consanguineous marriage family. Western blot verified the nonsense mutation. Results To identify disease-causing gene variants in a consanguineous Chinese pedigree with USH2C, DNA from proband was analyzed using targeted next generation sequencing (NGS). The patient was clinically documented as a possible USH2 by a comprehensive auditory and ophthalmology evaluation. We succeeded in identifying the deleterious, novel, and homologous variant, c.6912dupG (p.Leu2305Valfs*4), in the GPR98 gene (NM_032119.3) that contributes to the progression of USH2C. Variant detected by targeted NGS was then confirmed and co-segregation was conducted by direct Sanger sequencing. Western blot verified losing almost two-thirds of its amino acid residues, including partial Calx-beta, whole EPTP and 7TM-GPCRs at the C-terminus of GPR98. Furthermore, our results highlighted that this p.Leu2305Valfs*4 variant is most likely pathogenic due to a large deletion at the seven-transmembrane G protein-coupled receptors (7TM-GPCRs) domain in GPR98 protein, leading to significantly decreased functionality and complex stability. Conclusions These findings characterized the novel disease causativeness variant in GPR98 and broaden mutation spectrums, which could predict the pathogenic progression of patient with USH2C, guide diagnosis and treatment of this disease; and provide genetic counseling and family planning for consanguineous marriage pedigree in developing countries, including China.